Neutral Results Obtained in the ELIXA Trial. Issue 28 (29th October 2015) - Cunningham, Muriel
ELIXA was a randomized, double-blind, placebo-controlled trial among patients with type 2 diabetes mellitus who had experienced a recent acute coronary syndrome event. Lixisenatide was not superior to placebo in the primary composite end point of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, and hospitalization for unstable angina.